Necrotising Scleritis and Peripheral Ulcerative Keratitis Associated with Rheumatoid Arthritis Treated with Rituximab - Hardy, S.; Hashemi, K.; Catanese, M.; Candil, M.; Zufferey, P.; Gabison, E.; Guex-Crosier, Y. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Rheumatoid arthritis is a chronic and common inflammatory autoimmune disease. This primarily involves the synovia of the joints, but can cause many extra-articular manifestations as well, including peripheral ulcerative keratitis (PUK) and necrotising scleritis. These are often a threat to vision; they significantly compromise not only the eyeʼs structural integrity but are also important for prognosis and need urgent management. History and signs Three cases of peripheral ulcerative keratitis associated with rheumatoid arthritis were recorded in the electronic databank of the Jules Gonin Uveitis Clinic, two with necrotising scleritis and peripheral ulcerative keratitis and one with only peripheral ulcerative keratitis. They were all followed at Jules Gonin Eye Hospital (Lausanne, Switzerland), conjointly with the Department of Rheumatology at the Centre Hospitalier Universitaire Vaudois (Lausanne, Switzerland). Therapy and Outcome Good initial therapeutic response was observed in the two patients who received rituximab therapy. The patient who received only high dose corticosteroid developed massive colon perforation as well as acute renal insufficiency a few days after her ocular event. Conclusion From our limited number of patients, we found that the two patients who received the induction therapy with rituximab were stabilised from an ocular standpoint; however, rituximab had to be switched to other molecules, either due to other systemic symptoms from the disease itself or due to adverse effect of this treatment. This contributes to the increasing number of reports that rituximab can be an effective treatment for refractory ocular complications of rheumatoid arthritis (RA), at least as an induction therapy.
Keywords: rituximab; golimumab; abatacept; rheumatoid arthritis; necrotising scleritis; peripheral ulcerative keratitis; PUK